Electric field control of the reversible magnetocaloric effect in strain-mediated Ni37.5Co12.5Mn35Ti15/PMN-PT composite. (November 2021) - Qiao, Kaiming; Zuo, Shulan; Zhang, Hu; Hu, Fengxia; Yu, Ziyuan; Weng, Fan; Liang, Yuhang; Zhou, Houbo; Long, Yi; Wang, Jing; Sun, Jirong; Zhao, Tongyun; et al.
Abstract: In this study, the martensite transformation of Ni37.5 Co12.5 Mn35 Ti15 ribbon was studied and regulated by the electric field-induced strain in the PMN-PT substrate. The reversible magnetocaloric effect in the Ni37.5 Co12.5 Mn35 Ti15 /PMN-PT composite was enhanced by manipulating transition paths under the coupling of magnetic field and electric field, which is significantly important for applications in solid-state refrigeration. With the assistance of E = +8 kV/cm, the reversible entropy change increased from 19.5 to 25.7 J/kgK at 294.5 K. Meanwhile, the reversible cooling temperature span was also enlarged. Hence, the reversible refrigerant capacity was enhanced from 83 to 131 J/kg, and the increase ratio reached 58%. On this basis, an active magnetic regenerating cycle facilitated by an electric field was designed. This work provides an effective method for enhancing reversible caloric effects in first-order phase transition materials via electric fields. Graphical Abstract: Image, graphical abstract